Optical gain of CdxZn1−xTe quantum dot structures - Muwaffaq Abdullah; Baqer O. Al‐Nashy; Amin H. Al‐Khursan (Micro & Nano Letters, 2023)
Abstract Gain spectra of CdxZn1−xTe/AlGaN undoped and doped quantum dot (QD) structures are studied under the inhomogeneous broadening assumption at four Cd mole fractions (x=0.25,0.5,0.75,0.95). For the Cd0.25Zn0.75Te QD structure, two peaks appear due to the excited state (ES) and ground state (GS) transitions. The gain for the doped structures doubles the undoped ones. The gain increases while the wavelength is reduced with increasing Cd content due to the broader band discontinuity between the QD states. The discontinuity of the bands for each structure (mole fraction) is calculated, which is one of the merits of this work. While the structure Cd0.25Zn0.75Te offers the peak wavelengths 470 and 630 nm, other mole fractions offer the wavelengths between them. These visible bands are essential in different applications. The effect of QD size effect is also examined. The wavelength is extended by 20 nm for each 1 nm QD height increment.